2022
DOI: 10.1186/s12917-022-03207-6
|View full text |Cite
|
Sign up to set email alerts
|

TMT-based proteomic analysis reveals integrins involved in the synergistic infection of reticuloendotheliosis virus and avian leukosis virus subgroup J

Abstract: Background Co-infection with the avian leukosis virus subgroup J (ALV-J) and the reticuloendotheliosis virus (REV) increases mutual viral replication, causing a more serious pathogenic effect by accelerating the progression of neoplasia and extending the tumor spectrum. However, the molecular mechanism underlying the synergistic replication of ALV-J and REV remains unclear. Results Here, we performed this study to compare the differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…Some studies have reported an association of ITGA11 with infections. In an animal study, ITGA11 was associated with co-infection of avian leukosis virus subgroup J and reticuloendotheliosis virus in chicken embryos, and the study also suggests that ITGA11 was enriched in the pathways of virus-vector interaction, bio-adhesion, and immune responses at the protein level [38]. Similarly, our results of enrichment analysis also indicated that ITGA11 was relevant to protein binding.…”
Section: Discussionsupporting
confidence: 52%
“…Some studies have reported an association of ITGA11 with infections. In an animal study, ITGA11 was associated with co-infection of avian leukosis virus subgroup J and reticuloendotheliosis virus in chicken embryos, and the study also suggests that ITGA11 was enriched in the pathways of virus-vector interaction, bio-adhesion, and immune responses at the protein level [38]. Similarly, our results of enrichment analysis also indicated that ITGA11 was relevant to protein binding.…”
Section: Discussionsupporting
confidence: 52%